CONNECTION BETWEEN STUDENTS LEARNING MOTIVATION AND PERSONAL PECULIARITIES OF STUDENTS AND TEACHERS AND WORKING STYLE OF TEACHERS - Porozovs, Juris; Kristapsone, Silvija; Kauliņa, Anda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Proficiency of students obtained during teaching process in school determine their competitiveness in the labour market. One of the most important factor for raising students’ achievements is learning motivation. The survey of 482 teachers from different Latvia schools about students learning motivation was carried out. Study results showed that teachers consider that the most popular subjects among students are English language, informatics and sports. One of the most suitable teaching methods is laboratory works. Various factors influence students’ learning motivation but the most important of them are the interest about subject, the desire to make a career and sense of duty. The ability of teacher to create interest about subject depends from his or her attitude to students as well as from working style.